Análisis de la reducción del costo de consumo de energía eléctrica usando un sistema de Paneles Fotovoltaicos en los Laboratorios de la Facultad de Ingeniería de Sistemas e Informática de la UNSM – T - Pino Gutiérrez, Miguel Ángel (2015)
The following research, "ANALYSIS OF ELECTRIC ENERGY CONSUMPTION COST REDUCING USING A SYSTEM OF PHOTOVOLTAIC PANELS IN THE LABORATORY OF THE FACULTY OF ENGINEERING AND COMPUTER SYSTEMS OF UNSM - T"; had as objectives to compare the costs of consumption of the system of photovoltaic panels and conventional electricity, as his determination system using photovoltaic panels, high power energy consumption and cost on the use panel system was determined photovoltaic compared with conventional electrical energy in the laboratories of the Faculty of Engineering and Information Systems. The purpose of this research was oriented to providing updated and relevant information to FISI, to formulate oriented management and facing of strategies according to the results. The study was applied and transversal method was also applied experimental design: Pre and Posttest (with the same unit of analysis), the universe and the sample were constituted by 03 networks telematics laboratories and support. The instrument used was a direct observation card. So it was concluded that Hypothesis verification was performed with the t-student method; determining that the calculated T (3984) is greater than the tabulated t (1701). Therefore the alternative hypothesis is accepted, this fact allows us to state categorically that the use of photovoltaic panels system reduce the cost of electric energy consumption in the laboratories of the Faculty of Systems Engineering and Informatics, National University of San Martín for having achieved significant results